Introducing a Mobile Drug Formulary for Healthcare Professionals in Mauritius - Jheelan-Ramchandur, Ahinsa; Jodheea-Jutton, Abha; Nagowah, Leckraj (Journal of Health Informatics in Africa, 2020)
Background and Purpose: Prescribing errors and faults are common in medical practice and are more prevalent among young doctors. These are mainly due to erroneous medical decisions that can unfortunately cause much harm to the patients. This study aimed at developing a mobile Drug Formulary application for Mauritius with the view to promote e-health and medication safety in Mauritius.Methods: Drug information were sought from pharmacies and wholesalers. The medications were categorized anatomically and relevant information about each medication was retrieved from established databases such as the British National Formulary and Vidal. A mobile framework was designed which allowed an administrator to upload a list of drugs on a cloud environment and the mobile devices to connect to this environment on startup to download the updates, if any, to the local device.Results: A database has been created with the existing medications provided by participating wholesalers in Mauritius. An Android and iOS compatible mobile application was developed that linked to the database on the cloud and enabled loading of all information on demand.  A user-friendly prototype with access to comprehensive information about drugs currently available on the Mauritian market was implemented.Conclusions: This is the first initiative to develop an e-tool to facilitate the prescribing of medications in Mauritius.  Further work is underway to improve the database as well as setting up of a reliable strategy for updating of the database.